Efficient DNA Condensation by a C3‐Symmetric Codeine Scaffold. Issue 1 (13th December 2018) - McStay, Natasha; Reilly, Anthony M.; Gathergood, Nicholas; Kellett, Andrew
Abstract: A novel tripodal codeine scaffold (CC3 ) was rationally designed using computational methods as a DNA condensing alkaloid. Separation of the piperidine nitrogen atoms inCC3 is considerably larger at 14.36 Å than previously reported tripodal opioids allowing for enhanced aggregation of larger DNA plasmids (>4, 000 bp). The scaffold undergoes protonation at physiological pH that allows for controlled compaction and release of nucleic acids. Condensation is inhibited under basic conditions and nucleic acid release can be achieved by modulating the ionic strength. Zeta potential experiments indicate stabilised DNA particles at low alkaloid loading with AFM measurements showing particles sizes with a height of 103 nm and diameter of 350 nm. Since condensation is a prerequisite for the cellular uptake of DNA, this new class of alkaloid represents a novel nucleic acid condensation agent with potential gene therapy applications. Abstract : No pain and all gain ! A novel codeine molecule (CC3 ; see figure) is reported to have excellent DNA condensation properties. Aggregation can be controlled by modulating pH and release triggered by changing the ionic strength. AFM measurements ofCC3 ‐compacted plasmid DNA (2686 bp) show gene delivery particles with a height of 103 nm and diameter of 350 nm.